The future of punishment - Nadelhoffer, Thomas (Oxford series in neuroscience, law, and philosophy, 2013)
Desert and the justification of punishment / John Martin Fischer -- Brute retributivism / Shaun Nichols -- Free will skepticism and criminal punishment / Derk Pereboom -- Why do we resist hard incompatibilism, thoughts on freedom and punishment / Michael Louis Corrado -- Compatibilist criminal law / Stephen J. Morse -- Neuroscience, normativity, and retributivism / Michael S. Pardo and Dennis Patterson -- Cognitive neuroscience, moral responsibility, and punishment / Nancey Murphy -- Free will, science, and punishment / Alfred R. Mele -- The mind, the brain, and the law / Thomas Nadelhoffer and others -- Moralistic punishment as a crude social insurance plan / Eyal Aharoni and Alan J. Fridlund -- Punishing the addict: reflections on Gene Heyman / Neil Levy -- Free will, responsibility, and the punishment of criminals / Farah Focquaert , Andrea Glenn, and Adrian Raine